If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (8m + 7)((64(m * m)) + -56m + 49) Reorder the terms: 0 = (7 + 8m)((64(m * m)) + -56m + 49) Multiply m * m 0 = (7 + 8m)((64(m2)) + -56m + 49) Reorder the terms: 0 = (7 + 8m)(49 + -56m + (64m2)) Multiply (7 + 8m) * (49 + -56m + (64m2)) 0 = (7(49 + -56m + (64m2)) + 8m * (49 + -56m + (64m2))) 0 = ((49 * 7 + -56m * 7 + (64m2) * 7) + 8m * (49 + -56m + (64m2))) 0 = ((343 + -392m + 448m2) + 8m * (49 + -56m + (64m2))) 0 = (343 + -392m + 448m2 + (49 * 8m + -56m * 8m + (64m2) * 8m)) 0 = (343 + -392m + 448m2 + (392m + -448m2 + 512m3)) Reorder the terms: 0 = (343 + -392m + 392m + 448m2 + -448m2 + 512m3) Combine like terms: -392m + 392m = 0 0 = (343 + 0 + 448m2 + -448m2 + 512m3) 0 = (343 + 448m2 + -448m2 + 512m3) Combine like terms: 448m2 + -448m2 = 0 0 = (343 + 0 + 512m3) 0 = (343 + 512m3) Solving 0 = 343 + 512m3 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-512m3' to each side of the equation. 0 + -512m3 = 343 + 512m3 + -512m3 Remove the zero: -512m3 = 343 + 512m3 + -512m3 Combine like terms: 512m3 + -512m3 = 0 -512m3 = 343 + 0 -512m3 = 343 Divide each side by '-512'. m3 = -0.669921875 Simplifying m3 = -0.669921875 Reorder the terms: 0.669921875 + m3 = -0.669921875 + 0.669921875 Combine like terms: -0.669921875 + 0.669921875 = 0.000000000 0.669921875 + m3 = 0.000000000 The solution to this equation could not be determined.
| 9x+6=12x-15 | | 11x+11=4x+4+77 | | 13x-10=9x-15+33 | | 6[3a-3a(3a+3b)+9a^2]= | | (-6m^6n^2)(7mn^4)= | | 9x-15=13x-10+33 | | 0.01w=-0.045 | | 4x+8=90-4x | | (-2m^4n^5)(7mn^3)= | | 6x-12=4x+11 | | 140-4x=5x | | (8x)= | | 140-4x=10x+17 | | x^2-15x+65=11565 | | factorisem^2+7m-10=0 | | 5cos(x+17)=4 | | m^2+7m-10=0 | | 5(3x+2)=-5 | | 5x-9=111-10x | | x(4-x)=x^2(7-x) | | 13210*X^2+6785600*x-5315460000=0 | | 4(3x-1)=56 | | (-7m^5n^5)(5mn^2)= | | (-4a^6b^6)(3ab^3)= | | x^2+5y=x^2 | | (b^9c^5)(b^7c)= | | 180-x^2+x-5=7x+5 | | x-5+x+5=39 | | (m^10n^3)(m^12n)= | | 32*x^5+1=0 | | 3(3*3)=-27 | | x+8+x^2-3x+3x-2+x+2=43 |